Optical Games as Alternative Learning Media to Increase Students' Learning Interest in Interference and Light Diffraction Material - Bagus Pratama; Pangestu , Dimas Aji; Salsabilla, Sasqia Shafa (Impulse: Journal of Research and Innovation in Physics Education, 2022)
The COVID-19 pandemic, which has occurred for more than two years, has affected all aspects of life, including the world of education. Along with the increasingly sloping case of the spread of the COVID-19 virus, now many schools are starting to re-implement the offline learning system. Students accustomed to learning with an online pattern must get used to returning to learning with an offline pattern. In this transitional period, of course, various problems arise, one of which is the decline in student interest in learning. This study develops one of the learning media in the form of an application game to increase student interest in learning. This study aims to determine the feasibility of game-based learning media to increase student interest in light interference and diffraction. The research method used is the research and development method with the 4D model method. The findings in this study are games can be used as an alternative learning media to increase students' interest in learning the material. Based on the stages that have been carried out, the results of the feasibility test of the Instagram comic learning media product are declared very feasible.